Electric, thermal, and magnetic based digital interfaces for next generation food experiences. Issue 1 (2016) - Karunanayaka, Kasun; Cheok, Adrian David; Samshir, Nur Amira; Johari, Nurafiqah; Hariri, Surina; Rahman, Nur Ellyza Abd; Mustafa, Nur Ain; Anton, Prem
No abstract available